Salatiga Cassava tourism development strategy - Ahmad Fikri Sabiq (Indonesian Tourism Journal, 2024)
This study aims to determine the development of cassava Argowiyoto Salatiga Village. This research is a field research conducted in Cassava Village Argowiyoto, Ngaglik, Ledok, Argomulyo, Salatiga. Primary data sources come from field data obtained through interviews and observations. While the secondary data comes from written sources both in books, journals, and from online media. While the analysis of this study using descriptive analysis. Kampung Singkong Argowiyoto Ngaglik begins with Gethuk Kethek Dua Rasa which then develops with the existence of many culinary-based SMEs. This development continued with the emergence of cassava cheese D-9 as a tourist attraction. The next development is the emergence of Argotelo which develops educational and recreational aspects that are attractive to tourists. From the existing MSMEs, it then developed until dozens of MSMEs appeared in the Argowiyoto cassava Village area. Some of the strategies for developing cassava tourism are building a community of entrepreneurs, holding promotional events, cooperating with various parties, developing culinary variations, and using social media as a means of promotion